The Stigma of the Yutori Generation in the Drama Series “Yutori desu ga nani ka” - Linda Unsriana; Sandy Saputra (Universitas Diponegoro, 2025)
Yutori education is an educational system designed to reduce student pressure. This relaxed approach has led to the emergence of a new generation known as the